Commutation Time Estimator For PM BLDC Motor Torque Signature Enhancement - Wael, A. Salah; Ishak, Dahaman; Abu_Al_Aish, Amir; Abu Zneid, Basem; Abu Sneineh, Anees (Taylor's University, 2014)

(untitled)
This paper presents the development of the commutation time estimator (CTE) for PM BLDC motor drives. The proposed scheme is aimed to enhance motor output torque by minimizing the generated torque ripples. The torque ripples originating from commutation instances cause spikes and dips in the motor output torque. The motor output torque could be enhanced by mitigating the phase current mismatch rate during phase current commutation period. This rate could be almost matched by introducing the commutation time estimator (CTE) in order to control the rate of the energized phase current to be matched with the de-energized phase rate. Results obtained have validated and verified the proposed CTE effectiveness with a 50% average reduction of the generated torque ripples in PM BLDC motor.